Literatur review: Implementasi Marketing Mix 7P Terhadap Tingkat Kepuasan Pasien Di Rumah Sakit - Desi Natalia Marpaung; Ernawaty - Ernawaty; Diansanto - Prayoga; Syifa’ul - Lailiyah (Dian Nuswantoro Semarang, 2021)
The marketing mix is a marketing strategy used by hospitals to maximize service delivery to patients. The purpose of study was to analyze the effect of the 7P marketing mix (product, price, place, promotion, process, people, physical building) on patient satisfaction in the hospital. The method of writing literature review begins with selecting topics, determining keywords to find journal references. The databases used include Google Scholar, Elsevier, Portal Garuda, Shinta. Reference searches are limited from 2016 to 2020. The keywords used are